Association between improved metabolic risk factors and perceived fatigue during dietary intervention trial in relapsing-remitting multiple sclerosis: A secondary analysis of the WAVES trial - Villa, Aneli T.; Tu, Betty H.; Titcomb, Tyler J.; Saxby, Solange M.; Shemirani, Farnoosh; Ten Eyck, Patrick; Rubenstein, Linda M.; Snetselaar, Linda G.; Wahls, Terry L. (Frontiers in Neurology, 2023)
Background: Preliminary dietary intervention trials with the low-saturated fat (Swank) and modified Paleolithic elimination (Wahls) diets have shown favorable effects on fatigue among people with multiple sclerosis (MS); however, their impact on metabolic health is unknown. Objective: To evaluate the impact of the Swank and Wahls diets on markers of metabolic health and to determine the association between changes in metabolic health and perceived fatigue among people with relapsing-remitting MS (RRMS). Methods: As part of a randomized parallel-arm trial, vital signs and blood metabolic biomarkers were collected from participants with relapsing-remitting MS (n = 77) at four study visits spaced 12 weeks apart: 1) run-in, 2) baseline, 3) 12-weeks, and 4) 24-weeks. Participants followed their usual diet at run-in, then were randomized at baseline to either the Swank or Wahls diets and followed for 24 weeks. Results: Both groups had significant reductions in weight, body mass index (BMI), total cholesterol, and low-density lipoprotein (LDL) at 12- and 24-weeks compared to respective baseline values (p  0.04 for all). The Swank group also had a significant reduction in high-density lipoprotein (HDL) at 12- and 24-weeks (p = 0.0001 and p = 0.02, respectively), while the Wahls group had significant reductions in diastolic blood pressure (DBP) change in the cognitive subscale was not significant at 12-weeks in the Swank group (p = 0.06). Reductions in BMI, total cholesterol, and LDL were associated with corresponding reductions in total perceived, cognitive, and motor fatigue scores (p  0.05 for all). Weight and DBP reductions were associated with significant reductions in total and cognitive fatigue scores, while reductions in insulin and triglyceride levels were associated with significant reductions in total and motor fatigue scores (p  0.03 for all). Conclusion: Both diets lead to significant reductions in weight, BMI, total cholesterol, and LDL, which were associated with significant reductions in perceived fatigue.